2014
DOI: 10.1364/ol.39.006245
|View full text |Cite
|
Sign up to set email alerts
|

Ultra low-loss hypocycloid-core Kagome hollow-core photonic crystal fiber for green spectral-range applications

Abstract: We report on the development of a hypocycloidal-core Kagome hollow-core photonic crystal fiber guiding, with low transmission loss in the 450-650 nm visible spectral range. Transmission loss records have been achieved with 70  dB/km at 600 nm, and 130  dB/km at 532 nm. As a demonstration of the fiber potential applications, we report on a compact 600 THz wide Raman comb generator, centered around 532 nm, and on a 10 W average power frequency-doubled Yb-fiber picosecond laser beam delivery, along with its use f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 12 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…Actually, the hollow-core anti-resonant fiber (HC-ARF) and its leaky core mode have been investigated for decades [14][15][16]. However, only in recent years, the introduction of hypocycloid [17] or negative curvature [18] core-surround structures revived the development of HC-ARF since it enables coexistence of broadband light confinement (200-800 THz) and low transmission attenuation (20-100 dB/km depending on the wavelength) [19,20]. Furthermore, the spatial overlap of the core mode with the glass material is universally one order of magnitude smaller in HC-ARF than in HC-PBGF [21].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the hollow-core anti-resonant fiber (HC-ARF) and its leaky core mode have been investigated for decades [14][15][16]. However, only in recent years, the introduction of hypocycloid [17] or negative curvature [18] core-surround structures revived the development of HC-ARF since it enables coexistence of broadband light confinement (200-800 THz) and low transmission attenuation (20-100 dB/km depending on the wavelength) [19,20]. Furthermore, the spatial overlap of the core mode with the glass material is universally one order of magnitude smaller in HC-ARF than in HC-PBGF [21].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of hypocycloid core contour was a direct consequence of the IC mechanism where the fiber-core guidance is based on strongly reducing the optical overlap between the guided core mode and the continuum cladding modes. This in turn explains the loss reduction from a decibel per meter (dB/m) level in the first IC guiding HC-PCF, which took the form of a Kagome lattice cladding surrounding a hollow core with a circular [1] or a hexagonal core contour [2], to a tens of dB/km level in hypocycloid core-contour HC-PCF [3,5,11,16,17]. The impact of the corecontour geometry on the fiber confinement loss (CL) was detailed in [5], where it was shown that the larger the negative curvature of the core-contour cups, the lower the CL and fraction of the power overlap one can reach.…”
mentioning
confidence: 99%
“…The suitability of such fiber technology for USP lasers has been illustrated, for example, in the transport of 600-fs pulses at the millijoule energy level in robustly single-mode fashion using a 10-m-long piece of this IC Kagome HC-PCF [8]. Furthermore, this power and energy handling has been demonstrated with the most commonly used USP lasers, such as those based on Yb or Nd:Yag [8,9], on Ti:Sapphire (Ti:Saph) [10], or on frequency-doubled Yb [11] or Er [12]. Finally, any improvement in the transmission performance of these fibers will further improve the growing and spreading use of USP lasers in industrial applications as various as biophotonics [13], micro-machining [14] and micro-surgery [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…negative curvature) to hollow fibers [2], which allowed a dramatic drop in the transmission loss. Today, IC guiding hypocycloid-core Kagome HC-PCF outperforms their photonic bandgap (PBG) guiding counterparts in the NIR-VIS spectral range with record loss figures of 17 dB/km at ~1 µm wavelength range [3], 70 dB/km at ~780 nm [4] and 70 dB/km at 500-600 nm wavelength range [5]. Furthermore, even with a single ring cladding design [6], transmission loss of ~30 dB/km around 3-4 µm wavelength range were reported [7].…”
Section: Introductionmentioning
confidence: 99%